Correlation between Ecological Plasticity of Elite Winter Wheat Varieties and DNA Methylation Pattern Polymorphism within Variety - Kravets, O.P.; Sokolova, D.O.; Berestyana, A.M.; Shnurenko, O.R.; Bannikova, M.O.; Morgun, B.V.; Kuchuk, M.V.; Grodzinsky, D.M. (Science and Innovation, 2024)
The correlation between the ecological plasticity of the eight premium winter wheat varieties and the DNA methylation pattern polymorphism within variety has been studied using the seedlings from seeds with different germination rate. Polymorphism degree or “epigenetic distance” in restriction fragment range of PCR products has been assessed using Nei index. The correlation between variety grade determined by its productivity and ecological plasticity and the degree of DNA methylation pattern polymorphism within variety (Rs=0.69) has been found. The prevalence of the greatest “epigenetic distance” (D≥0.1) in the most productive and ecologically plasticized varieties has been proved. The “epigenetic distance” assessment has been recommended to apply to the selection of new varieties for the areas with unstable climate conditions.